Improving endurance exercise performance at high altitude: Traditional and nontraditional approaches - Salgado, R. M.; Ryan, B. J.; Seeley, A. D.; Charkoudian, N. (Exercise and Sport Sciences Reviews, 2025)
Acute exposure to terrestrial altitude (hypobaric hypoxia) causes decrements in endurance performance relative to sea level. Altitude acclimatization consistently results in partial attenuation of these decrements, but due to logistical challenges, it is not readily implemented. We discuss mechanisms and impact (or lack thereof) of other non-acclimatization interventions to improve endurance performance and provide suggestions for future research directions.